Human Security Implications and the Indonesian Diaspora in the Philippines - Harakan, Ahmad; Said, Try Gustaf (International Journal of Demos (IJD), 2023)
AbstractThe present research endeavours to explore the ramifications of the Indonesian diaspora in the Philippines on human security. It scrutinises the encounters of Indonesian migrants and their probable effects on the security dynamics of individuals, communities, and regions. This article employs an interdisciplinary methodology, utilising sources such as policy reports, and academic literature. The present study initiates by examining the underlying determinants that propel Indonesian migration towards the Philippines, including but not limited to economic prospects, social connections, and geopolitical dynamics. The subsequent discussion pertains to the difficulties encountered by the Indonesian diaspora, encompassing issues of assimilation into society, the availability of educational and medical resources, and instances of prejudice. The research subsequently analyses the implications of these challenges on human security, with a specific focus on three dimensions: (1) the security and well-being of individuals; (2) the cohesion of communities and social stability; and (3) the dynamics of regional security. The results underscore the interrelatedness of these aspects and underscore the necessity of a thorough and interdisciplinary strategy in tackling the human security issues that emerge from the existence of the Indonesian diaspora in the Philippines. The article concludes by underscoring the significance of a cooperative endeavour among the governments of Indonesia and the Philippines, civil society organisations, and the global community to alleviate the adverse effects of migration and advance the welfare of the Indonesian diaspora and the communities where they reside.Keywords: Human Security, Indonesian Diaspora, Social, Political DimensionsÂ AbstrakPenelitian ini berupaya untuk mengeksplorasi konsekuensi diaspora Indonesia di Filipina terhadap keamanan manusia. Ini meneliti pertemuan para migran Indonesia dan kemungkinan dampaknya terhadap dinamika keamanan individu, komunitas, dan wilayah. Artikel ini menggunakan metodologi interdisipliner, memanfaatkan sumber-sumber seperti laporan kebijakan, dan literatur akademik. Studi ini dimulai dengan mengkaji faktor-faktor penentu yang mendorong migrasi Indonesia menuju Filipina, termasuk namun tidak terbatas pada prospek ekonomi, hubungan sosial, dan dinamika geopolitik. Pembahasan selanjutnya berkaitan dengan kesulitan yang dihadapi oleh diaspora Indonesia, meliputi masalah asimilasi ke dalam masyarakat, ketersediaan sumber daya pendidikan dan medis, dan contoh prasangka. Penelitian selanjutnya menganalisis implikasi dari tantangan ini terhadap keamanan manusia, dengan fokus khusus pada tiga dimensi: (1) keamanan dan kesejahteraan individu; (2) kohesi komunitas dan stabilitas sosial; dan (3) dinamika keamanan kawasan. Hasilnya menggarisbawahi keterkaitan aspek-aspek tersebut dan menggarisbawahi perlunya strategi yang menyeluruh dan interdisipliner dalam mengatasi masalah keamanan manusia yang muncul dari keberadaan diaspora Indonesia di Filipina. Artikel ini diakhiri dengan menggarisbawahi pentingnya upaya kerja sama antara pemerintah Indonesia dan Filipina, organisasi masyarakat sipil, dan komunitas global untuk mengurangi dampak buruk migrasi dan memajukan kesejahteraan diaspora Indonesia dan masyarakat di mana mereka tinggal..Kata Kunci: Keamanan Manusia, Diaspora Indonesia, Dimensi Sosial dan Politik